Phương pháp đơn giản điều chế bột nano N-TiO2 có hoạt tính quang xúc tác cao dưới nguồn ánh sáng nhìn thấy - Hưng, Nguyễn Văn; Lê, Đặng Thị Thanh (Vietnam Journal of Chemistry, 2014)
Nitrogen-doped nanosized TiO2 powders were prepared by a simple thermal treatment method of the mixture of titanium dioxide and urea. The prepared products were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), UV-Vis diffuse reflectance spectra (UV-Vis-DRS) and Fourier transform infrared (FT-IR) spectroscopy. The results showed that the crystal structure of N-TiO2 was a mixture of anatase and rutile phases, and the average particle size was 31 nm calculated from XRD results. The UV–vis spectra indicate an increase in absorption of visible light when compared to undoped TiO2. The photocatalytic activity of nitrogen-doped TiO2 powder was evaluated by the decomposition of methylene blue under visible light irradiation. And it was found that nitrogen-doped TiO2 powders exhibited much higher photocatalytic activity than undoped TiO2. Moreover, the study also showed that, the doping N atoms improve the growth of the TiO2 crystal and phase transformation.